2020
DOI: 10.1002/ldr.3836
|View full text |Cite
|
Sign up to set email alerts
|

Ploughing/zero‐tillage rotation regulates soil physicochemical properties and improves productivity of erodible soil in a residue return farming system

Abstract: In residue return farming, ploughing and zero‐tillage (syn. no‐till or minimal tillage) rotation may regulate soil physicochemical properties and help reduce erosion and improve productivity; however, the soil physicochemical properties and soil productivity response to ploughing and zero‐tillage rotation remain unclear. This present study evaluates the effects of ploughing and zero‐tillage rotation on soil physicochemical properties and crop productivity based on an 11‐year experiment (2007–2018) on a typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This was attributed by reduced soil bulk density and increased soil moisture content. Conservational and preparation method have been found to increase maize yield by 10.4%, 11%, 10.8% and 38% respectively [71,72,73,74].…”
Section: Effects Land Preparation Methods and Organic Amendment On Ma...mentioning
confidence: 99%
“…This was attributed by reduced soil bulk density and increased soil moisture content. Conservational and preparation method have been found to increase maize yield by 10.4%, 11%, 10.8% and 38% respectively [71,72,73,74].…”
Section: Effects Land Preparation Methods and Organic Amendment On Ma...mentioning
confidence: 99%
“…Although some studies suggest that seeding in no-till or tilled land benefits yield, the results obtained in this study, as well as those obtained by Pittelkow et al [68], argue that minimum tillage and no tillage should be combined with other conservation agricultural measures to exercise a positive effect on yield. In the research carried out by Wang et al [69], it emerged that the no-tillage system had no significant effect on maize yield. However, following the research carried out by Liu et al [70] in a semi-arid area of the Loess Plateau of China from 2014 to 2016, it was concluded that applying the no-tillage system increases the water capacity and bulk density of the soil, but soil porosity and maize yield are reduced.…”
Section: Maize Yields Obtained In Relation To the Experimental Factorsmentioning
confidence: 99%
“…At the same time, microbial communities attracted by cover crop roots (living mulch) can improve soil nutrient availability and water accessibility and produce stimulating substances, thus supporting corn growth and increasing productivity [22]. Wang et al [34] also found that not tilling had no significant effect on maize yield; however, the yield changed when combined with cover crop retention. Furthermore, it was observed that different utilization methods for cover crops have different effects on silage maize yield.…”
Section: Impact Of Different Tillage and Cover Measures On Maize Yiel...mentioning
confidence: 99%